Impact of Oil Factor on Consumer Market: The Case of Azerbaijan - Humbatova, Sugra; Gadim, Ibrahim Guliyev; Mileddin, Sabuhi Tanriverdiyev; Hajiyev, Natig Gadim-Oglu (International Journal of Energy Economics and Policy, 2023)
This article investigates the long ‒term and short ‒term interactions between crude oil and oil products export, and consumer market, retail trade, public catering, paid services and retail trade turnover per person of population in Azerbaijan using annual data from 1997 to 2021. In this research, the ARDL model was used to assess co ‒integration and short ‒term relationships. In addition, this study used the FMOLS, DOLS, and CCR co ‒integration equations to explore long ‒term coefficients between variables. Granger causation tests were performed, Granger causation analysis was assessed using the Wald test (short ‒term or weak causation, long ‒term causation, and both short ‒term and long ‒term causation or strong causal relationship). The study proposed 5 hypotheses regarding the impact of oil and oil products export, and consumer market, retail trade, public catering, paid services and retail trade turnover per person of population. Some of the hypotheses were generally, if not completely, justified. Based on the established models and tests carried out, there are co ‒integrating relationships between the variables. Model coefficients are selected according to their economic and statistical significance.